The instrumented timed up and go test: potential outcome measure for disease modifying therapies in Parkinson's disease - Zampieri, Cris; Salarian, Arash; Carlson-Kuhta, Patricia; Aminian, Kamiar; Nutt, John G; Horak, Fay B (Journal of neurology, neurosurgery and psychiatry, 2010)
The Timed Up and Go (TUG) test has been used to assess balance and mobility in Parkinson's Disease (PD). However, it is not known if this test is sensitive to subtle abnormalities present in early stages of the disease, when balance and gait problems are not clinically evident but may be detected with instrumented analysis of movement. We hypothesise that postural transitions and arm swing during gait will be the most sensitive characteristics of the TUG for early PD. In the present study, we instrumented the TUG test (iTUG) using portable inertial sensors, and extended the walking distance from 3 m (traditional TUG) to 7 m. Twelve subjects with early-to-moderate, untreated PD and 12 healthy individuals participated. Our findings show that although the stopwatch measure of TUG duration did not detect any abnormalities in early-to-mid-stage PD, the peak arm swing velocity on the more affected side, average turning velocity, cadence and peak trunk rotation velocity were significantly slower. These iTUG parameters were also correlated with the Unified Parkinson's Disease Rating Motor Scale. Thus, the iTUG test is sensitive to untreated PD and could potentially detect progression of PD and response to symptomatic and disease-modifying treatments.